2008
DOI: 10.1128/jb.00945-08
|View full text |Cite
|
Sign up to set email alerts
|

SciN Is an Outer Membrane Lipoprotein Required for Type VI Secretion in EnteroaggregativeEscherichia coli

Abstract: Enteroaggregative Escherichia coli (EAEC) is a pathogen implicated in several infant diarrhea or diarrheal outbreaks in areas of endemicity. Although multiple genes involved in EAEC pathogenesis have been identified, the overall mechanism of virulence is not well understood. Recently, a novel secretion system, called type VI secretion (T6S) system (T6SS), has been identified in EAEC and most animal or plant gram-negative pathogens. T6SSs are multicomponent cell envelope machines responsible for the secretion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
197
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 196 publications
(203 citation statements)
references
References 74 publications
4
197
0
Order By: Relevance
“…We recently reported coimmunoprecipitation data that identify four components, TssL, TssM, TssJ, and TagL, constituting the membrane-asso- ciated subcomplex (27). Although TssJ is an outer membrane lipoprotein (12), the three other components are anchored in the inner membrane. TssM interacts with TssJ, and this interaction has been characterized through different approaches (29,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently reported coimmunoprecipitation data that identify four components, TssL, TssM, TssJ, and TagL, constituting the membrane-asso- ciated subcomplex (27). Although TssJ is an outer membrane lipoprotein (12), the three other components are anchored in the inner membrane. TssM interacts with TssJ, and this interaction has been characterized through different approaches (29,31).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the translocation of canonical protein effectors degrading the peptidoglycan layer into the periplasm of recipient bacterial cells has been demonstrated (10,11). The T6SS has also been shown to be involved in stress sensing or biofilm formation, although the mechanistic bases for these phenotypes have not been described yet (12)(13)(14). The T6SS is therefore a versatile machine that adapts to the specific needs of each bacterium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Type T6SS proteins have been identified that correspond to orthologous components in phage tails that include the tail spike, tube, sheath, and base plate (4,6). Innerand outer-membrane-associated T6SS proteins likely anchor the T6SS organelle to the cell envelope (8)(9)(10). Because the functionality of the T6SS apparatus has been correlated with its ability to kill or inhibit both eukaryotic as well as prokaryotic cells, most models for T6SS function postulate that the contraction of the sheath minimally ejects a complex corresponding to the T6SS spike/tube complex out of the T6SS + cells and into target cells in close contact (4,6).…”
mentioning
confidence: 99%
“…The components constituting this multiprotein secretion complex are beginning to be defined. On the basis of work in several organisms, the T6SS IcmF ortholog seems to be a central scaffolding protein that interacts with itself, the T6SS DotU ortholog, and a T6SS-encoded outer membrane lipoprotein (6)(7)(8). In V. cholerae, T6SS proteins VipA and VipB form a tubular structure that is dissociated by ClpV protein in an ATP-dependent manner (9), which could be required for biogenesis of a functional secretion complex.…”
mentioning
confidence: 99%